2012
DOI: 10.1029/2012gl053551
|View full text |Cite
|
Sign up to set email alerts
|

First observations of 5fce auroral roars

Abstract: [1] Auroral radio emissions reveal physics of beam-plasma interactions and provide possibilities to remotely sense ionospheric plasma processes. Sato et al. (2012) recently discovered that auroral roar emissions, long known to occur at two and three times the electron gyrofrequency ( f ce ), also occur at 4f ce . Using data from wave receivers in the British Antarctic Survey Automatic Geophysical Observatories, we confirm the existence of 4f ce -roars and observe for the first time 5f ce -roars. A search at hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
3
9
0
Order By: Relevance
“…An interesting trend is evident: 2 f ce emissions occur exclusively after sunset and before sunrise, i.e., under darkness conditions as has been extensively documented in the literature [e.g., Weatherwax et al , ; LaBelle and Weatherwax , ]. Conversely, 4 f ce and 5 f ce emissions occur exclusively in daylight as previously shown by Sato et al [] and LaBelle [], and 3 f ce emissions occur both in darkness and daylight. There is a clear indication of onset of higher harmonics at higher solar zenith angles.…”
Section: Experiments Resultssupporting
confidence: 67%
“…An interesting trend is evident: 2 f ce emissions occur exclusively after sunset and before sunrise, i.e., under darkness conditions as has been extensively documented in the literature [e.g., Weatherwax et al , ; LaBelle and Weatherwax , ]. Conversely, 4 f ce and 5 f ce emissions occur exclusively in daylight as previously shown by Sato et al [] and LaBelle [], and 3 f ce emissions occur both in darkness and daylight. There is a clear indication of onset of higher harmonics at higher solar zenith angles.…”
Section: Experiments Resultssupporting
confidence: 67%
“…The vast majority of the observed 4 f c e roar emissions, 86 of 88, occur during sunlit conditions, 78 of these occurring during the 6 months bracketing summer solstice (i.e., between 21 March and 21 September). This result confirms the tendency of 4 f c e roar emissions to occur in sunlit conditions as first shown by Sato et al [, Figure 3b] and confirmed by LaBelle [, Figure 2]. From this study, the occurrence rate of 4 f c e emissions in the interval 16–00 UT is approximately 5% under sunlit conditions (6006 min of 4 f c e roar in 2015 h) versus 0.06% under darkness conditions (15 min in 449 h), i.e., factor of hundreds is less likely to be observed in darkness conditions than in daylit conditions.…”
Section: Data Presentationsupporting
confidence: 91%
“…As pointed out in several previous papers [e.g., Sato et al , , ; LaBelle , ; LaBelle and Dundek , ], sunlit conditions usually imply higher electron densities in the F region which allow the matching condition f u h = N f c e to occur for higher harmonics N of the electron cyclotron frequency. For this reason, generation of higher cyclotron harmonic emissions through mode conversion of upper hybrid waves stimulated at the matching condition in the presence of unstable auroral electron distribution functions occurs favorably during daytime, whereas this mechanism can directly produce only lower harmonics at nighttime when densities are lower.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Indeed, the measured polarization of 2 f c e and 3 f c e is consistent with this interpretation in that the L ‐ O mode polarization is dominant for these emissions [ Shepherd et al , ; Sato et al , ]. Recently, 4 f c e [ Sato et al , ] and 5 f c e [ LaBelle , ; LaBelle and Dundek , ] auroral roars have also been detected near the sunlit side of the ionosphere where the electron density is enhanced via photoionization.…”
Section: Introductionsupporting
confidence: 56%